Non-coding RNAs as Regulators of Cellular Senescence in Idiopathic Pulmonary Fibrosis and Chronic Obstructive Pulmonary Disease - Omote, Norihito; Sauler, Maor (Frontiers in Medicine, 2020)
Cellular senescence is a cell fate implicated in the pathogenesis of idiopathic pulmonary fibrosis (IPF) and chronic obstructive pulmonary disease (COPD). Cellular senescence occurs in response to cellular stressors such as oxidative stress, DNA damage, telomere shortening, and mitochondrial dysfunction. Whether these stresses induce cellular senescence or an alternative cell fate depends on the type and magnitude of cellular stress, but also on intrinsic factors regulating the cellular stress response. Non-coding RNAs, including both microRNAs and long non-coding RNAs, are key regulators of cellular stress responses and susceptibility to cellular senescence. In this review, we will discuss cellular mechanisms that contribute to senescence in IPF and COPD and highlight recent advances in our understanding of how these processes are influenced by non-coding RNAs. We will also discuss the potential therapeutic role for targeting non-coding RNAs to treat these chronic lung diseases.